Recurrent urinary infection with Bifidobacterium scardovii - Barberis, Claudia (2012)
Bifidobacterium species are difficult to identify and may be underreported or not recovered by many laboratories because of their slow growth. We emphasize the importance of the Gram stain in urine samples and the addition of enriched media and enhanced atmosphere over time for urine cultures with pyuria. This is the first report of a Bifidobacterium scardovii recurrent urinary infection in an elderly woman. Copyright © 2012, American Society for Microbiology. All Rights Reserved.